Ovicidal and adulticidal activities of Cymbopogon citratus (DC.) Stapf and Illicium verum Hook. f. against Aedes aegypti (Linn.) - Puwanard, C.; Soonwera, M. (International Journal of Agricultural Technology, 2022)
The hatching inhibition and knockdown rates against Aedes aegypti of two essential oils (EOs): Cymbopogon citratus DC. Stapf and Illicium verum Hook F was evaluated. The efficacy of each of these EOs, at 1, 5, 10% emulsion in water, stabilized by tween 60®, was compared to that of 1% w/v temephos and 1% w/w cypermethrin (common, harmful synthetic insecticides). Topical and contact assays showed that 10% C. citratus and 10% I. verum emulsions were the most effective in inhibiting the hatching of mosquito eggs (100%) after 48 hours of exposure. Moreover, they were also the most toxic against mosquito adults (100% mortality) after 24 hours of exposure. This study also established that tween 60® had no effect on hatching inhibition or mortality rate of treated Aedes aegypti mosquitoes. All EO emulsions were more potent than temephos and cypermethrin against these mosquito species. Coupling this higher efficacy with no or benign known side effects of natural EOs, it can be concluded that 10% C. citratus and 10% I. verum emulsions are better alternatives than temephos and cypermethrin for a mosquito control program at the present time.